The Impact of Transformational Leadership on Performance Appraisal - Zarina Akbar, Chandra Kusuma (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the impact of transformation all leadership on performance appraisal. This study uses a quantitative approach ex-post-facto method. The measuring instrument used to measure transformational leadership style is the Transformational Leadership Questionnaire from the Multifactor Leadership Questionnaire (MLQ) developed by Bass and Avolio (2004). The questionnaire used to measure employee performance appraisa laws adapted based on performance measurement criteria. The sampling technique is done by using non-probability sampling. The sample of this research is 10 9employees.The statistical ethodused  to analyze the data of this study is the regression analysis. The results showed that there was a significant influence of transformational leadership on the performance appraisalofemployees.Theinfluenceoftransformationalleadershiponemployeeperformance appraisal was 46.3%. The higher the leadership style that focuses on developing the overall value system of employees, then the higher the employee performance will be.Keywords: transformational leadership, performance appraisal, employee.